Influence of impurity boron on water resistance of basic magnesium sulfate cement. Issue 1 (1st August 2022) - Zhang, Xiaoyuan; Wu, Chengyou
Abstract: In this study, magnesium hydroxide was used as the precursor of magnesium oxide, mixed with different amounts of boric acid, and then calcined at 700°C and 1000°C to prepare different active magnesium oxide, and then BMSC specimens were obtained. By analyzing the effect of impurity boron on the compressive strength, microscopic morphology, hydration products, etc. of BMSC before and after soaking in water, the effect of impurity boron on the water resistance of BMSC was further explored. The results showed that the impurity boron had a great influence on the water resistance of BMSC. Th 1 e compressive strength of BMSC containing impurity boric acid decreased significantly after soaking in water, but its hydration product remained unchanged as 5·1·7 phase. Magnesium activity is low, crystallinity is low, and the dissolution rate of MgSO4 in the 5·1·7 phase is inversely proportional to the degree of crystallinity.